HUBUNGAN KOMPETENSI BIDAN, PENERAPAN SOP PERSALINAN DAN KELENGKAPAN PERALATAN MEDIS DENGAN KESELAMATAN IBU MELAHIRKAN DI WILAYAH KERJA PUSKESMAS BANDAR PETALANGAN KELURAHAN RAWANG 4 - Rofi Faniasih; Agus Triyono (Jurnal Kesehatan dan Kedokteran, 2023)
Maternal Mortality Rate or commonly abbreviated as AKI is the number of maternal deaths during pregnancy, childbirth and childbirth caused by pregnancy, childbirth and childbirth or their management but not due to other causes such as accidents or falls in every 10,000 live births. The MMR rate is influenced by many factors such as the lack of competence of midwives, not fully implementing SOPs for deliveries and existing facilities such as completeness of medical equipment that supports the safety of mothers in childbirth according to the law in an effort to reduce the MMR so that it increases the degree of better health. The purpose of this study was to determine the relationship between the competence of midwives, delivery SOPs and completeness of medical equipment with the safety of mothers giving birth in the working area of ​​the Bandar Petalangan Health Center, Rawang 4 Village, in 2022. The sampling technique was carried out to all midwifery staff as many as 30 respondents and 30 respondents to mothers who gave birth. From the results of the study it was found that there was a significant relationship between the competence of midwives and the safety of the mother giving birth (p=0.004), there was a significant relationship between SOP for delivery and the safety of the mother giving birth (p=0.003), there was a significant relationship between the completeness of medical equipment and the safety of the mother gave birth (p=0.001). Based on the results of this study, it can be suggested to always maintain and update the completeness of medical equipment, carry out the entire process with delivery SOPs, and regularly conduct training for midwives